Identification structure of the mating‐type locus and distribution of Kabatiella zeae in China. Issue 1 (12th October 2020) - Chen, Nan; Sun, Jiaying; Liu, Kexin; Jiang, Pengcheng; Wang, Fen; Fu, Dandan; Xiao, Shuqin; Ma, Changguang; Zhang, Shuping; Xue, Chunsheng
Abstract: The 51 isolates, the causing agents of maize eyespot, were identified as Kabatiella zeae with morphological and molecular methods. The structure of the MAT locus in K. zeae JLMHK‐9 strain contains MAT1‐1 and MAT1‐2 genes which are transcribed in opposite directions, DNA lyase gene ( APN2 ) which is adjacent to the 3′ flanking region of MAT1‐2‐1 gene and a pleckstrin homology domain (PH) which is adjacent to the 3′ flanking region of MAT1‐1‐1 gene. The specific primers are used to identify the mating types of K. zeae isolates collected from six provinces in China, and our findings speculate that K. zeae is a homothallic species.